2020
DOI: 10.4102/hsag.v25i0.1468
|View full text |Cite
|
Sign up to set email alerts
|

Traditional birth attendants’ experiences during the provision of post-natal care in Mopani District, Limpopo province of South Africa

Abstract: Background South African maternity care guidelines stipulate that post-natal patients can be discharged within 6 h after delivery, provided that the condition of mothers and neonates do not require medical, surgical or obstetric attention. Hence in many instances post-natal care is rendered at home by traditional birth attendants (TBAs). Traditional birth attendants play a crucial role in the care of women during pregnancy, birth and puerperium within communities. Aim T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Also, there are limited studies that have explored the spatial distribution of the utilisation of unskilled birth services in SSA. The available studies on unskilled birth attendants were mostly focused on only single countries in Africa, e.g., Olakunde, Adeyinka (5) for Nigeria, or explored perceptions of women about unskilled birth attendants from a qualitative perspective, e.g.,-Gurara, Muyldermans (7) for Ethiopia, and Selepe and Thomas (8) for South Africa [7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Also, there are limited studies that have explored the spatial distribution of the utilisation of unskilled birth services in SSA. The available studies on unskilled birth attendants were mostly focused on only single countries in Africa, e.g., Olakunde, Adeyinka (5) for Nigeria, or explored perceptions of women about unskilled birth attendants from a qualitative perspective, e.g.,-Gurara, Muyldermans (7) for Ethiopia, and Selepe and Thomas (8) for South Africa [7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…This premise has also been determined in previous studies, which is explained by the bad experience that pregnant women have inside the institutions, which motivates them to change the place of delivery (44). In this regard, initiatives have been proposed that incorporate traditional midwives within (inside) the institution, where they can establish educational discussions, due to it has been identified that the usual clinical environment does not allow to establish appropriate communication (45)(46)(47). These proposals can be applied to improve care, which would improve adherence to institutional care, where there are tools to sort out complications in a timely manner.…”
Section: Discussionmentioning
confidence: 89%
“…The traditional midwives' role is providing community care and getting people closer to the biomedical health system. To reach this goal, it is important to offer both parties, biomedical and traditional health staff, the necessary tools to attain their objectives [7,8]. One of the tools is education based on community needs, where midwives are able to make decisions and improve care coverage.…”
Section: Open Accessmentioning
confidence: 99%